2006
DOI: 10.1021/ar050107x
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Raman Scattering in Local Optical Fields of Silver and Gold NanoaggregatesFrom Single-Molecule Raman Spectroscopy to Ultrasensitive Probing in Live Cells

Abstract: This Account discusses surface-enhanced Raman scattering at extremely high enhancement levels that can occur for molecules attached to silver and gold nanoclusters. Strongly enhanced and highly confined local optical fields enable surface-enhanced Stokes and anti-Stokes Raman spectroscopy of single molecules even under nonresonant excitation conditions as well as extremely large effective cross sections in two-photon excited Raman spectroscopy. The ability for very sensitive and spatially confined molecular st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
501
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 638 publications
(511 citation statements)
references
References 57 publications
7
501
0
3
Order By: Relevance
“…Among various metal nanoparticles, gold (Au) is the most widespread material used in optics, electrochemistry, catalysis, and biochemical sensing because it is stable, less toxic and biocompatible [1][2][3][4]. A lot of techniques have been developed for the synthesis of Au nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Among various metal nanoparticles, gold (Au) is the most widespread material used in optics, electrochemistry, catalysis, and biochemical sensing because it is stable, less toxic and biocompatible [1][2][3][4]. A lot of techniques have been developed for the synthesis of Au nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…However, Ag is considered unstable, degrades in vivo and is typically synthesized with cetrimonium bromide (CTAB), which is considered cytotoxic [282][283][284]. Additionally, it has been demonstrated that the peak intensity ratios of the Raman signal change significantly when silver aggregates are used leading to inconsistent results and poor reproducibility [276,[285][286][287].…”
Section: Surface Enhanced Raman Scattering (Sers) and Electromagneticmentioning
confidence: 99%
“…They are considered to have many advantages over traditional enzyme linked immunosorbent assays (ELISAS) which are considered tedious, time consuming, and rely on the use of toxic and unstable fluorescent dyes and quantum dots (QDs) [282,[315][316][317]. It is known that SERS has equal or in some cases a greater enhancement of Raman signal when compared to fluorescent markers and that SERS metal substrates produce spectral line widths which are 10-100 times narrower compared to fluorescence [64,318,319].…”
Section: Sers Immunoassaysmentioning
confidence: 99%
“…51 From this equation, one could see the distances of the SERS substrate and reporters, the surface densities of the reporters, and the dispersing state of the tags, as a reviewer indicated. Experimental results revealed that the tag was monodispersed in each test condition.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 99%